Latin America and Caribbean - Southern Cone Inland Waterways Transportation Study The Paraguay-Paraná Hidrovía : Its Role in the Regional Economy and Impact on Climate Change - World Bank (World Bank, 2012)
The Paraguay-Parana rivers waterway system (referred to in the text as the Hidrovia, or HPP) is potentially the greatest axis for freight movement in the sub-region and a possible integration mechanism for the Southern Common Market (MERCOSUR) countries. However, 90 percent of freight in the sub-region is moved by road transport, a significantly inefficient mode of transport in terms of fuel consumption, space use and greenhouse gas (GHG) emissions. For over 15 years the Southern cone countries have attempted to coordinate their regulations and policies to improve the navigability of the HPP so that it can reach its full potential. These efforts have been marred by failures and disputes that have resulted in no concrete actions. Given the apparently limited investment needed to make the HPP the principal low-cost, low-impact freight transport system in the sub-region, it is worthwhile to investigate why the HPP has been unable to fulfill its promise. This report attempts to determine why the Hidrovia, one of most significant watercourses in South America, is underutilized. This study analyzes the HPPs role in freight movement and trade in the subregion. It further looks at the technical, economic and environmental feasibility of the improvements and defines what will be required to implement improvements. In the analysis of environmental impacts, the GHG emissions per mode of transport, particularly fluvial transport, are estimated in order to define the HPP's overall climate change impact. Next, it describes the institutional context and assesses the institutional arrangements in each country and the coordination efforts that have been attempted. Finally, it outlines several areas of intervention that the World Bank could explore to collaborate with this endeavor.